Metode Customer Relationship Management untuk Stokis Luxor Cabang Kisaran Berbasis Web - Cici Paramita Panjaitan; Iqbal Kamil Siregar; Santoso Santoso (J-Com (Journal of Computer), 2021)
Abstract : Customer relationship management is a facility to strengthen relationship between companies and customers. CRM also establishes sales programs to build and manage close ties with customers so as not to move to other competitors. This thesis presents an increase in web-based CRM in Stockist Luxor Kisaran. Luxor Stockist is a business entity engaged in marketing herbal products, the system used is still with a manual system. The results of the fundamental method on the web obtained are managing customer data, product improvement, product sales, and consumer consultation facilities to respond to questions and suggestions from customers. This application uses the PHP and MYSQL programming language for the media to make it easier for customers to interact with the company. This application is expected to help companies strengthen the good word with customers in retaining customers and to get new customers. Keyword :Customer Relationship Management, Marketing, Services, PHP language and  MYSQL database  Abstrak : Manajemen hubungan pada pelanggan ialah suatu fasilitas guna  mempererat jalinan baik perusahaan dan pelanggan. CRM juga membentuk program penjualan guna membangun serta mengatur ikatan yang erat pada pelanggan agar tidak berpindah ke pesaing lain. Skripsi ini menyajikan peningkatan CRM berbasis web di Stokis Luxor Kisaran. Stokis Luxor merupakan badan usaha yang bergerak dalan pemasaran produk herbal, sistem yang digunakan masih dengan sistem manual. Hasil metode mendasar pada web yang didapat adalah mengatur data konsumen, peningkatan produk, penjualan produk, dan fasilitas konsultasi konsumen guna menanggapi pertanyaan maupun saran dari pelanggan. Aplikasi ini memakai bahasa program PHP dan MYSQL untuk media agar memudahkan pelanggan untuk berinteraksi dengan perusahaan.. Aplikasi ini diharap dapat membantu perusahaan dalam mempererat ikataan baik dengan pelanggan dalam mempertahankan pelanggan dan untuk mendapatkan pelanggan baru.Kata Kunci:Customer Relationship Management,Pemasaran ,Pelayanan, bahasa PHP dan database MYSQL